Māori Experiences of Physical Rehabilitation in Aotearoa New Zealand: A Scoping Review - Sheehy, Becky; Wepa, Dianne; Collis, Julie M (Taylor and Francis Group, 2024)
PURPOSE: The purpose of this review was to explore what is currently known about Māori experiences of physical rehabilitation services in Aotearoa New Zealand. METHODS: A scoping review was undertaken following steps described by the Joanna Briggs Institute. Databases and grey literature were searched for qualitative studies that included descriptions of Māori consumer experiences in their encounters with physical rehabilitation. Data relating to study characteristics were synthesised. Qualitative data were extracted and analysed using reflexive thematic analysis. RESULTS: Fourteen studies were included in this review. Four themes were generated that describe Māori experiences of rehabilitation. The first theme captures the expectations of receiving culturally unsafe care that become a reality for Māori during rehabilitation. The second theme describes whānau as crucial for navigating the culturally alien world of rehabilitation. The third theme offers solutions for the incorporation of culturally appropriate Māori practices. The final theme encompasses solutions for the provision of rehabilitation that empowers Māori. CONCLUSIONS: This scoping review highlights ongoing inequities experienced by Māori when engaging with rehabilitation services. Strategies for facilitating culturally safe rehabilitation for Māori have been proposed. It is essential that rehabilitation clinicians and policymakers implement culturally safe approaches to rehabilitation with a view to eliminating inequities in care provision and outcomes for Māori.
Keywords: Cultural safety; Māori; qualitative; rehabilitation; scoping review; Cultural safety; Māori; qualitative; rehabilitation; scoping review; 4201 Allied Health and Rehabilitation Science; 4203 Health Services and Systems; 42 Health Sciences; Rehabilitation; Physical Rehabilitation; 8.1 Organisation and delivery of services; 7.1 Individual care needs; Generic health relevance; 11 Medical and Health Sciences; Rehabilitation; 32 Biomedical and clinical sciences; 42 Health sciences; 44 Human society; Humans; Cultural Competency; Culturally Competent Care; Maori People; New Zealand; Qualitative Research; Rehabilitation; Humans; Rehabilitation; Qualitative Research; New Zealand; Cultural Competency; Culturally Competent Care; Maori People; Humans; Cultural Competency; Culturally Competent Care; Maori People; New Zealand; Qualitative Research; Rehabilitation